A CORRELATION BIOMARKER BETWEEN BMI AND LIPID PEROXIDATION IN TYPE 2 DIABETES MELLITUS WITH AND WITHOUT OTHER COMPLICATIONS - KHAN , M; NOUMAN, M; HASHIM , H; LATIF , S; HUSAIN, S; SATTAR , S; KHATOON , F (Biological and Clinical Sciences Research Journal, 2023)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder associated with several complications, such as cardiovascular disease and retinopathy. Objective: The main objective is to find the correlation between body mass index (BMI) and lipid peroxidation biomarkers in T2DM patients with and without complications. This cross-sectional study involves 50 T2DM patients, with 25 patients having complications and 25 without complications. The study was conducted at Nishtar Medical University and Hospital from August 2022 to February 2023. BMI and lipid peroxidation biomarkers were measured, including malondialdehyde (MDA) and 4-hydroxynonenal (4-HNE). T2DM patients with complications had a significantly higher BMI and higher levels of MDA and 4-HNE compared to those without complications. A positive correlation was observed between BMI and lipid peroxidation biomarkers in both groups of T2DM patients. Furthermore, T2DM patients with complications had significantly higher levels of fasting blood glucose, HbA1c, total cholesterol, LDL cholesterol, triglycerides, and serum creatinine, and lower levels of HDL cholesterol compared to those without complications. Our study highlights the importance of managing BMI and oxidative stress in preventing and managing T2DM complications. More studies are required to find the mechanisms underlying the association between BMI and lipid peroxidation in T2DM patients and to investigate the potential therapeutic implications of managing BMI and oxidative stress in T2DM patients.